1997
DOI: 10.1177/002204269702700110
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Risk for HIV Transmission among Drug Abusers in Porto Alegre, Brazil

Abstract: The authors describe the preliminary data from a research project to assess risk behaviors for HIV transmission among drug abusers in the south of Brazil, with particular emphasis on IDUs. Two questionnaires developed by U.S. researchers (the risk for AIDS behavior inventory {RAB} and the risk behavior assessment [RBAJ] were translated and adapted to be used as assessment tools for the first 61 cases of the project. The preliminary findings are reported, as well as implications for the development of future in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
3
0
1
Order By: Relevance
“…Baseline and follow-up assessments included the Addiction Severity Index (ASI), 9,10 to assess the impact and severity of their drug use in different life areas (selected variables of the ASI were used for analysis); the Symptom Check List-90 (SCL-90), 11 which evaluates nine dimensions of psychiatric symptoms (for the purpose of this study, only the general score was utilized); the Beck Depression Inventory (BDI) 12,13 ; and selected individual items of the Brazilian version of the Risk Assessment Battery (RAB ), [14][15][16][17][18] a self-report instrument that measures drug use and sexual behaviors associated with HIV risk. The Brazilian version of the RAB that was used in this study did not have a specific section on injection practices since preliminary studies done when adapting the instrument to Brazil showed no heroin use and few cocaine injection practices.…”
Section: Data Collectionmentioning
confidence: 99%
“…Baseline and follow-up assessments included the Addiction Severity Index (ASI), 9,10 to assess the impact and severity of their drug use in different life areas (selected variables of the ASI were used for analysis); the Symptom Check List-90 (SCL-90), 11 which evaluates nine dimensions of psychiatric symptoms (for the purpose of this study, only the general score was utilized); the Beck Depression Inventory (BDI) 12,13 ; and selected individual items of the Brazilian version of the Risk Assessment Battery (RAB ), [14][15][16][17][18] a self-report instrument that measures drug use and sexual behaviors associated with HIV risk. The Brazilian version of the RAB that was used in this study did not have a specific section on injection practices since preliminary studies done when adapting the instrument to Brazil showed no heroin use and few cocaine injection practices.…”
Section: Data Collectionmentioning
confidence: 99%
“…Os 570 sujeitos deste estudo são provenientes do processo amostral de um estudo de natureza similar, que visava conhecer os comportamentos e situações associadas a maior soropositividade de usuários de droga sistemáticos que estivessem fazendo uso regular de drogas no mês prévio à coleta de dados 13,14,15,16,17 . O uso regular foi definido como ter utilizado substân-cias psicoativas quase sempre ou todos os dias no mês prévio à coleta, o que era aferido pelo questionário sobre comportamentos de risco para AIDS.…”
Section: Critérios De Inclusão E Coleta De Dadosunclassified
“…After all revisions, a second version -that incorporated the suggestions of the initial collectors -was developed and tested in a convenience sample with 61 volunteers in different places in Porto Alegre. 16 After the definition of the version to be used in the fieldwork, one of the authors made a back trans-lation into English. Copies were sent to US partners who revised the translation and found that questions did not differ significantly from their original English format.…”
Section: Instrumentmentioning
confidence: 99%
“…While the instrument was validated, data collection was performed using the CRA in 695 subjects with similar features, in order to generate data about the rate of seropositivity and epidemiological elements for another study. From the first 235 cases initially assessed in a preliminary analysis, 16 we built a frequency curve of total scores obtained from the simple addition of each answer of the instrument. We identified three main intervals (low, medium and high) of the total score to be used as initial parameters of the analysis.…”
Section: Construction Of the Frequency Curve Of The Cras For The Overmentioning
confidence: 99%